2021
DOI: 10.3389/fmicb.2020.613963
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase R Restricts the Intracellular Survival of Mycobacterium tuberculosis by Promoting Selective Autophagy

Abstract: Tuberculosis (TB) is a deadly infectious lung disease caused by the pathogenic bacterium Mycobacterium tuberculosis (Mtb). The identification of macrophage signaling proteins exploited by Mtb during infection will enable the development of alternative host-directed therapies (HDT) for TB. HDT strategies will boost host immunity to restrict the intracellular replication of Mtb and therefore hold promise to overcome antimicrobial resistance, a growing crisis in TB therapy. Protein Kinase R (PKR) is a key host se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
(119 reference statements)
2
17
1
Order By: Relevance
“…It is worth noting that the overall effect of PKR during M. tuberculosis infection may be context dependent. Although our findings and the results from Ranjbar et al indicate that PKR limits M. tuberculosis survival in vitro (97,98), a recent report using sst1-susceptible mice suggests that PKR contributes to macrophage necrosis in TB granulomas (119). sst1-susceptible mice develop necrotic inflammatory lung lesions similar to human TB granulomas, whereas their congenic B6 counterparts do not (120).…”
Section: Mycobacterium Tuberculosis Complexcontrasting
confidence: 71%
See 4 more Smart Citations
“…It is worth noting that the overall effect of PKR during M. tuberculosis infection may be context dependent. Although our findings and the results from Ranjbar et al indicate that PKR limits M. tuberculosis survival in vitro (97,98), a recent report using sst1-susceptible mice suggests that PKR contributes to macrophage necrosis in TB granulomas (119). sst1-susceptible mice develop necrotic inflammatory lung lesions similar to human TB granulomas, whereas their congenic B6 counterparts do not (120).…”
Section: Mycobacterium Tuberculosis Complexcontrasting
confidence: 71%
“…Salmonella Typhimurium can infect both humans and animals, and infection is commonly acquired by consuming contaminated food products. S. Typhimurium infection has been observed to increase mRNA levels of EIF2AK2 in MEFs ( 108 ), and we and others have reported that S. Typhimurium increases total and phosphorylated PKR protein levels in macrophages ( 87 , 98 ). These findings suggest that PKR plays a role in the antibacterial response to Salmonella .…”
Section: Pkr In Gram-negative Bacterial Infectionsmentioning
confidence: 69%
See 3 more Smart Citations